Perancangan Sistem Informasi Inventaris Barang Berbasis Web Secara Online Pada Universitas Prima Indonesia - Dhanny Rukmana Manday; Steven Wijaya; Jefrin Waruwu (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The importance of inventory management for business success and how technology can help improve inventory management. The design of an online web-based inventory information system at Prima Indonesia University is discussed in this article. The research aims to improve inventory management business profitability at Prima Indonesia University. One of the approaches used to collect data for this project is the waterfall system development process, which also includes interviews, observations, documentation, and literature studies. Blackbox testing is a technique used to test the system in publication. Functional testing verifies that the system can operate according to the functional requirements established during the analysis and design stages. Testing the system's ability to meet non-functional criteria, such as security, speed, and performance, is known as non-functional testing. After testing, the author makes improvements and fixes to the system found during testing. The support and maintenance stages are carried out regularly to ensure the system runs well and meets user needs. The results showed that the web-based online inventory system developed for Prima Indonesia University using the waterfall model can help improve inventory management and business profitability. The system can reduce errors in inventory management and speed up the process of searching and retrieving inventory data. System testing shows that the system can function properly and meet the requirements at the analysis and design stages.